Model Corporate Social Responsibility Mushaf Publishing: A Study Of The Cordoba-Baznas Quran Alms Program In Educating The Ummah - E. Kusman; Ahmad Sukandar (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study aims to evaluate the effectiveness of the Corporate Social Responsibility (CSR) model implemented by Quran Cordoba–BAZNAS in enhancing tajwīd literacy, tafsīr comprehension, and the motivational and emotional engagement of the public—particularly young people—with the Qur’ān. A mixed-methods design was employed: quantitatively, pre- and post-tests of tajwīd literacy (N = 200) and a five-point Likert questionnaire measuring motivational and affective outcomes; qualitatively, in-depth interviews with CSR program stakeholders, Islamic education faculty, and workshop participants. Quantitative data were analyzed using paired t-tests, while qualitative data underwent thematic analysis. Results indicate a statistically significant improvement in tajwīd scores (Δ +20.7; p < 0.01) and tafsīr comprehension, with 87% of participants reporting increased motivation for regular Qur’ān study and 92% reporting stronger emotional attachment to the Qur’ān following workshops in calligraphy, structured tadabbur, and “Quran Hour.” The partnership with higher-education institutions under the Tri Dharma framework enhanced program design, ensured academic rigor, and secured sustainable evaluation processes. In conclusion, the Cordoba–BAZNAS CSR model transcends mere mushaf distribution to function as a comprehensive Qur’ān-learning ecosystem, delivering measurable cognitive and affective outcomes. This “Educational CSR” paradigm is recommended as a best practice for publishers and religious organizations seeking to empower Qur’ān literacy in Indonesia.